2022
DOI: 10.3390/ph15121465
|View full text |Cite
|
Sign up to set email alerts
|

Norbornene and Related Structures as Scaffolds in the Search for New Cancer Treatments

Abstract: The norbornene scaffold has arisen as a promising structure in medicinal chemistry due to its possible therapeutic application in cancer treatment. The development of norbornene-based derivatives as potential chemotherapeutic agents is attracting significant attention. Here, we report an unprecedented review on the recent advances of investigations into the antitumoral efficacy of different compounds, including the abovementioned bicyclic scaffold in their structure, in combination with chemotherapeutic agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 154 publications
0
3
0
Order By: Relevance
“…On the other hand, many norbornene derivatives were reported to possess various biological activities, showing application potential in medicinal or agrochemical fields. For instance, a recent review reported a variety of norbornene derivatives and complexes, which displayed considerable antitumor activity against different cancer cells [24,25] . Concerning antifungal agrochemicals, commercial fungicides isopyrazam and benzovindiflupyr, which contain the norbornene group, display broad spectrum of antifungal activity toward several fungi on vegetables and fruits [26] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, many norbornene derivatives were reported to possess various biological activities, showing application potential in medicinal or agrochemical fields. For instance, a recent review reported a variety of norbornene derivatives and complexes, which displayed considerable antitumor activity against different cancer cells [24,25] . Concerning antifungal agrochemicals, commercial fungicides isopyrazam and benzovindiflupyr, which contain the norbornene group, display broad spectrum of antifungal activity toward several fungi on vegetables and fruits [26] .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a recent review reported a variety of norbornene derivatives and complexes, which displayed considerable antitumor activity against different cancer cells. [24,25] Concerning antifungal agrochemicals, commercial fungicides isopyrazam and benzovindiflupyr, which contain the norbornene group, display broad spectrum of antifungal activity toward several fungi on vegetables and fruits. [26] Moreover, Shatirova et al have synthesized amine-containing acetylene compounds of norbornene, and some of the derivatives displayed good inhibition against the growth of sulfatereducing bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Furthermore, norbornene and related structures have drawn increasing attentions as non-aromatic and nonplanar motifs in drug design, in attempts to afford variations in the so-called 'flatland drugs'. 22 Many norbornene derivatives have been reported to exhibit a broad spectrum of biological activities, such as antibacterial, 23 antiviral, 24 anticancer, 25 anti-inflammatory 26 and anticholinergic activities. 27 Concerning fungicidal agents, two commercial fungicides benzovindiflupyr and isopyrazam containing the norbornene group displayed a broad spectrum of antifungal activity toward different pathogenic fungi on grains, vegetables and fruits.…”
Section: Introductionmentioning
confidence: 99%